Carbonized chilli stalk adsorbent to remove methylene blue dye from aqueous solution: Equilibrium and kinetics studies. Issue 1 (May 2021) - Aziz, A; Hassan, H; Yahaya, N K E M; Karim, J; Ahmad, M A; Karim, K A
Abstract: The fast growth of textile industry has led to afflictive water pollution problems. The discharge of dyes into the environment poses health threats to the ecosystem due to their carcinogenicity and mutagenicity. Adsorption process is among the most utilized approach in treating textile wastewater. Chilli stalk which is abundantly available as agrowaste was transformed into adsorbent through carbonization process at various temperatures for the adsorption of methylene blue (MB). Dye batch adsorption studies were conducted to evaluate the effects of initial dye concentration (25 – 300 mg/L), contact time (0 – 24 hours) and carbonization temperature (350 - 400 °C). The surface characteristics, proximate and elemental analyses, surface morphology and chemistry were studied on both chilli stalk (CS) and carbonized chilli stalk adsorbent (CCSA). The maximum MB dye removal was 97.04% at 400 °C of carbonization temperature. The data fitted Freundlich isotherm model and pseudo-second-order kinetic model for adsorption equilibrium and kinetic studies, respectively.